Use of inorganic fertilizer on climate-smart crops improves smallholder farmers' livelihoods: Evidence from Western Kenya - Collins M. Musafiri; Milka Kiboi; Joseph Macharia; Onesmus K. Ng'etich; Michael Okoti; Betty Mulianga; David K. Kosgei; Abdirahman Zeila; Felix K. Ngetich (Social Sciences and Humanities Open, 2023)
The main challenges facing smallholder farmers in sub-Saharan Africa (SSA) are soil fertility decline and climate change, culminating in increased food insecurity. The double effect of climate change and soil fertility decline could be devastating among the poor rural smallholder farmers, who solely depend on rain-fed agriculture with little investment in adaptive mechanisms. Using inorganic fertilizers and careful selection of climate-resilient crops such as sorghum could improve the livelihoods of smallholder farmers through improved soil health and crop yields. However, information on the effects of inorganic fertilizer on sorghum production remains uncertain, especially in SSA. We evaluated the effects of inorganic fertilizers on sorghum yields among smallholder farmers in Western Kenya. We conducted a cross-sectional survey and collected data from 300 smallholder sorghum farmers. We employed a multi-stage sampling procedure to collect data from the specific smallholder farmers from the target population. We employed endogenous switching regression (ESR) modeling to control observed and unobserved bias in predicting the effects of inorganic fertilizer use on productivity. Smallholder farmers applied a limited amount of inorganic fertilizer. We established that hired labor, agricultural training, and farmers' perception of soil erosion were significant positive determinants of inorganic fertilizer use. Location and access to weather forecast information were key negative determinants of inorganic fertilizer use. The use of inorganic fertilizer increased crop yields by 14%. The findings suggested that inorganic amendments could promote food security and improve purchasing power, thus enhancing smallholder farmers' capacity to cope with declining soil fertility and climate change-related challenges. Therefore, agricultural policies targeting improved productivity of smallholder sorghum farmers could enhance inorganic fertilizer use while considering the determinants.